Pengembangan Sensor Kloramfenikol Berbasis Bovine Serum Albumin menggunakan Spektrofotometri UV (The Development of Chloramphenicol Sensor Based on Bovine Serum Albumin using Spectrophotometry UV) - Sarah Aisha; Bambang Kuswandi; Dwi Koko Pratoko (Pustaka Kesehatan, 2018)
Misuse of antibiotics has been discovered in shrimp exported from Indonesia, one of them is chloramphenicol, therefore it is necessary to develop methods for chloramphenicol detection. In this study, the chemical sensor for chloramphenicol detection has been developed. The sensor developed by immobilized bovine serum albumin (BSA) onto cellulose acetate membrane. The sensor has linear range of 6-16 μg/ml chloramphenicol with r 0.999 and limit of detection (LOD)-limit of quantification (LOQ) value of 0.74-2.21 μg/ml. The RSD value of repeatability and intermediet precision were 2.41% and 2.31%, where the recovery was 100.29%. Three of the five samples of tiger shrimp on the market containing chloramphenicol at level of 1.03; 2.48; and 3 μg/ml. The result also shown in good agreement with conventional spectrophotometry UV-Vis method. Keywords: shrimp, chloramphenicol, BSA, cellulose acetate